The effect of ice breaking on student learning outcomes in science subjects in Class IV of the PAB 1 Klumpang private elementary school - Syuhada, Intan Jelita; Tumiyem, Tumiyem; Sari, Dewi Purnama (Institute of Computer Science (IOCS), 2024)
This is the aim of this research to find out how much influence the Ice Breaking learning strategy has on students' science learning outcomes. By using a pre-test and post-test control group design, the data is processed in the form of numbers, so that this research process is a type of quantitative experiment. This research involved 40 students from class IV of PAB 1 Kumpang Kebun Private Elementary School. Data normality test, homogeneity test, and independent sample T-test were used for data analysis, which was carried out both before and after testing. Furthermore, based on statistical data, a significant value of 0.007 <0.05 was found, which indicates rejection of Ho and acceptance of Ha. Thus, it can be concluded that the Ice Breaking Learning Strategy has an impact on students' science learning outcomes.